Long-term sovereign interest rates in Czechia, Hungary and Poland: A comparative assessment with an affine term structure model - Jakub Janus (Statistics in Transition new series (SiTns), 2022)
This paper provides a comparative evaluation of the behaviour of long-term sovereign yieldsin Czechia, Hungary and Poland from 2001 to 2019. An affine term structure model de-veloped by Adrian, Crump and Moench (2013) is used as an empirical framework for thedecomposition of the bond yields into term premium and risk-neutral components. We docu-ment a substantial compression in term premia which started in Central European economiesaround 2013 and played a decisive role in the changes that occurred in 10-year sovereignyields. This pattern, however, was more prevalent in Czechia and Poland than in Hun-gary. We show that long-term rates in all three economies remained higher than in Ger-many due to relatively large risk-neutral components. Nevertheless, cross-country corre-lations became increasingly dependent on term premium dynamics, both among CentralEuropean economies and between each of them and Germany. These results are robust tobias-correction in the baseline models and interpreted in the light of the general interest ratesdecline in the global economy. Potential policy implications are also discussed.
Keywords: 519; long-term interest rates; affine term structure model; term premium; risk-neutralrates; Central Europe